Bangladesh : 2017 Article IV Consultation-Press Release; Staff Report. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2017)
This 2017 Article IV Consultation highlights steady monetary policy management and fiscal discipline in Bangladesh, which have supported macroeconomic stability, allowing the economy to benefit from favorable external demand, high remittances, and low commodity prices. The result has been strong output growth, falling inflation, moderate public debt, and a rebuilding of external resilience. In fiscal year 2017, output growth is expected to remain close to 7 percent. Over the medium term, maintaining output growth of about 7 percent a year would require increased public and private investment, as well as reforms to support capital market development and improved investment efficiency.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet